2018
DOI: 10.1002/pbc.27487
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of long‐term growth and bone development in pediatric and adolescent patients receiving bevacizumab

Abstract: Background We conducted an integrated analysis of clinical data to describe long‐term effects of bevacizumab on growth and bone development in pediatric and adolescent patients with solid tumors. Procedure Clinical data were pooled from five phase I/II trials of bevacizumab versus chemotherapy: BERNIE, HERBY, and AVF4117s enrolled newly diagnosed patients, AVF3842s and AVF2771s enrolled patients with relapsed/refractory disease. Height, weight, body mass index (BMI), and bone‐age data were pooled by treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Gerber et al [10] showed that VEGF-mediated capillary invasion is an important signal that regulates growth plate morphogenesis and triggers cartilage remodeling. However, Müller et al [20] observed no negative effects of bevacizumab on growth and development in pediatric and adolescent patients receiving bevacizumab and chemotherapy, which has been used in various types of cancer, compared with those receiving chemotherapy alone. We are unaware of any study showing the intra-articular effect of bevacizumab on joint development in children.…”
Section: Discussionmentioning
confidence: 99%
“…Gerber et al [10] showed that VEGF-mediated capillary invasion is an important signal that regulates growth plate morphogenesis and triggers cartilage remodeling. However, Müller et al [20] observed no negative effects of bevacizumab on growth and development in pediatric and adolescent patients receiving bevacizumab and chemotherapy, which has been used in various types of cancer, compared with those receiving chemotherapy alone. We are unaware of any study showing the intra-articular effect of bevacizumab on joint development in children.…”
Section: Discussionmentioning
confidence: 99%
“…14 As seen in preclinical studies, long-term use of bevacizumab has the potential to lead to growth plate or epiphyseal abnormalities, although it has yet to be reported in pediatric clinical studies, likely because bevacizumab has yet to be used in a sustained way. 15 Molecular characterization has further elucidated our understanding of pLGG with the majority of pLGG harboring driver mutations in the ratsarcoma virus/mitogen-activated protein kinase pathway. 5 With the advent of molecular data regarding BRAFV600E and BRAF fusion mutations, mitogen-activated protein kinase kinase inhibitors have emerged as an adjunct therapy for pLGG.…”
Section: Discussionmentioning
confidence: 99%
“…The most reported side effects of bevacizumab in the literature include proteinuria, hypertension, epistaxis, and fatigue 14. As seen in preclinical studies, long-term use of bevacizumab has the potential to lead to growth plate or epiphyseal abnormalities, although it has yet to be reported in pediatric clinical studies, likely because bevacizumab has yet to be used in a sustained way 15. Molecular characterization has further elucidated our understanding of pLGG with the majority of pLGG harboring driver mutations in the rat-sarcoma virus/mitogen-activated protein kinase pathway 5.…”
Section: Discussionmentioning
confidence: 99%
“…As some of these agents move forward and are being evaluated in front line studies, there is a greater need to continue growth plate monitoring (96,97). Although a pooled analysis of children receiving bevacizumab showed no negative effects on growth velocity, height, or body mass index (98), longer followup of patients treated with these drugs is needed to determine long term effects on growth and development.…”
Section: Linear Growth With Imatinib and Other Tkismentioning
confidence: 99%